2017
DOI: 10.1002/aqc.2777
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Asian clam distribution pattern reveals minimal constraints to downstream dispersal and imperceptible ecological impacts

Abstract: 1. The Asian clam Corbicula fluminea is an invasive freshwater species that can cause adverse ecological and economic impacts. Information on its dispersal abilities, ecological preferences and impacts may contribute towards the improvement of management strategies, including those relating to regulatory demands such as the European Water Framework Directive (WFD).2. Both the above perspectives were addressed through inspection of environmental constraints to C. fluminea dispersal and impacts in a semi-natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 80 publications
2
4
0
Order By: Relevance
“…Our results are consistent with the latest study of Pereira et al. (2017), which suggests that sediment characteristics are weaker predictors of corbiculid distribution per se.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with the latest study of Pereira et al. (2017), which suggests that sediment characteristics are weaker predictors of corbiculid distribution per se.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, it has been assumed that the presence of C. fluminea on higher grain size sediments is indeed related to the degree of oxygenation, which is always higher in coarse sediments (Castañeda et al, 2018;McMahon, 1999). Our results are consistent with the latest study of Pereira et al (2017), which suggests that sediment characteristics are weaker predictors of corbiculid distribution per se.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In one side, Selego et al (2012) also reported collector-gatherers replacement by collectorfilterers after river restoration efforts. In contrast, Pereira et al (2017) reported an apparent association between both functional feeding groups. Hence, conclusions in this regard would be speculative and further manipulative work may be needed to clarify functional feeding groups association.…”
Section: Discussionmentioning
confidence: 75%
“…The published literature on competition between native bivalves (mainly the Unionoida) and Corbicula is extensive, but conclusions regarding the effects of this interaction are often different (Miller & Payne, ; Vaughn & Spooner, , and references therein). Similarly, although Corbicula has been traditionally regarded as posing a serious threat to native biodiversity and ecosystem functioning, with possible environmental and economic repercussions (Sousa, Rufino, Gaspar, Antunes, & Guilhermino, ), recent research also suggests negligible ecological impacts (Pereira et al, ). In this vein, Corbicula and Cyanocyclas do coexist at present in four out of the five remaining local populations.…”
Section: Discussionmentioning
confidence: 99%